Analysis of the conduction mechanisms of the Ni doped apatite‐type lanthanum silicate electrolyte ceramics synthesized by the combustion method. Issue 3 (19th November 2021) - Chen, Shi; Huang, ZhiLiang; Chen, ChangLian; Hu, Pu; Huang, JiangSheng; Jiang, Yuan; Lu, Lu; Xia, Yan
Abstract: In this study, the nickel doped apatite‐type lanthanum silicate La9.33 Si6‐ x Ni x O26‐ x ( x  = 0, .5, 1.0, 1.5, 2.0) (LSNO) electrolyte powders were successfully generated by using the urea nitrate combustion method at 600°C and 6–8 min. The optimal sintering temperature was determined to be 1500°C on the basis of the linear shrinkage, relative density as a function of temperature, and microcosmic analysis. It was observed that Ni 2+ successfully replaced Si 4+ in [SiO4 ] to form the [Si(Ni)O4 ] tetrahedra. LSNO had a typical p63 /m apatite structure of high purity. A significant change in the cell volume of the doped samples was observed, and the cell volume increased with the doped nickel content. The conductivity reached the peak value at x  = 1.0 (1.21 × 10 −3 S·cm −1, 700°C). Nickel doping introduced the oxygen vacancies and expanded the channels for interstitial oxygen conduction. Further, it also directly reduced the amount of interstitial oxygen in the LSO structure. This led to an enhancement in the conductivity of La9.33 Si6‐ x Ni x O26‐ x, followed by a decrease on increasing the doped nickel content. The conductivity enhancement in the Ni‐doped LSO resulted from the combination of two mechanisms, namely, the oxygen vacancy defect and lattice volume enhancement mechanism.